Fluid-kinetic model of a propulsive magnetic nozzle. (3rd November 2021) - Merino, Mario; Nuez, Judit; Ahedo, Eduardo
Abstract: A kinetic-electron, fluid-ion model is used to study the 2D plasma expansion in an axisymmetric magnetic nozzle in the fully-magnetized, cold-ion, collisionless limit. Electrons are found to be subdivided into free, reflected, and doubly-trapped sub-populations. The net charge current and the electrostatic potential fall on each magnetic line are related by the kinetic electron response, and together with the initial profiles of electrostatic potential and electron temperature, determine the electron thermodynamics in the expansion. Results include the evolution of the density, temperature, and anisotropy ratio of each electron sub-population. The different contributions of ions and electrons to the generation of magnetic thrust are analyzed for upstream conditions representative of different thruster types. Equivalent polytropic models with the same total potential fall are seen to result in a slower expansion rate, and therefore to underpredict thrust generated up to a fixed section of the magnetic nozzle.